Tale of Geographical Indication Tag for Basmati - Murai, Ashish Santosh; Mamgai, Preeti; Bhadauria, Prgya; Kumar, Arvind (Indian Farming, 2018)
Farmers, especially the rural youth, can be retained in agriculture only if they are provided with enough incentives for their time and efforts. Agricultural products like Basmati rice are the symbol of Indian agriculture and future of Indian agriculture can only be secured through protecting these items from any kind of theft.